The Role of Animal Assisted Intervention on Improving Self-Esteem in Children With Attention Deficit/Hyperactivity Disorder - Schuck, Sabrina E. B.; Johnson, Heather L.; Abdullah, Maryam M.; Stehli, Annamarie; Fine, Aubrey H.; Lakes, Kimberley D. (Frontiers in Pediatrics, 2018)
Self-esteem across multiple domains as measured by the Self-Perception Profile for Children (SPPC; Harter, 1985; 2012) was evaluated in a recently completed randomized controlled trail examining Animal Assisted Intervention (AAI) with dogs for children with Attention Deficit/Hyperactivity Disorder (AHD) (n= 80, ages 7-9, 71% male). Baseline, mean ratings across all domains of the SPPC were consistent with that of published means for same age peers. All children rated themselves favorably, resulting in a non-normal distribution of scores. To test the hypothesis that AAI improves self-esteem, stratified Wilcoxon Signed-Rank Tests (SAS NPAR1WAY procedure) were used to compare pre- to post-treatment ratings. Analyses indicated that scores of children’s self-perceptions in the domains of behavioral conduct, social, and scholastic competence, were significantly increased from baseline to post-treatment in the AAI group (Z = -2.320, p = .021, Z = -2.631, p = .008 and Z = -2.541, p = .011, respectively), whereas pre-post-treatment differences in self-perceptions were not found for the children in the treatment group without dogs. Findings for each SPPC sub-scale and respective correlations to skills of Executive Function (EF) and parent ratings of behavior are discussed. Immediate future directions include examining associations between improved self-perception and observed self-regulation in the course of intervention.